2013 IEEE Conference on Computer Vision and Pattern Recognition 2013
DOI: 10.1109/cvpr.2013.43
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Super-Resolution of Depth and Images Using a Single Camera

Abstract: In this paper, we propose a convex optimization framework for simultaneous estimation of super-resolved depth map and images from a single moving camera. The pixel measurement error in 3D reconstruction is directly related to the resolution of the images at hand. In turn, even a small measurement error can cause significant errors in reconstructing 3D scene structure or camera pose. Therefore, enhancing image resolution can be an effective solution for securing the accuracy as well as the resolution of 3D reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…[35] proposes to approximate piecewise smooth functions in frame domain with sparse representation, and a tight frame based scheme is developed to recover depth image from noise and outliers corrupted data. [30] presents a convex optimization framework to simultaneously estimate super-resolution of both depth images and color images, in which the problem is formulated into a single energy minimization with a convex function. Similarly, [18] proposes to utilize the depth cues from the induced optical-flow to enhance the depth images captured by a moving device.…”
Section: Application To Joint Color and Depth Image Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] proposes to approximate piecewise smooth functions in frame domain with sparse representation, and a tight frame based scheme is developed to recover depth image from noise and outliers corrupted data. [30] presents a convex optimization framework to simultaneously estimate super-resolution of both depth images and color images, in which the problem is formulated into a single energy minimization with a convex function. Similarly, [18] proposes to utilize the depth cues from the induced optical-flow to enhance the depth images captured by a moving device.…”
Section: Application To Joint Color and Depth Image Reconstructionmentioning
confidence: 99%
“…Furthermore, the RGB-D camera may produce a severely noised color image under some bad illumination conditions. Thus the enhancement of depth image and RGB-D image is receiving increasing research interest [18,24,30,35]. We will employ the proposed multi-channel data-driven tight frame for the joint task of restoration of the depth image and noise removal of the color image.…”
Section: Introductionmentioning
confidence: 99%
“…They up-sample the depth map to the desired resolution (same factor as used at encoder), then performing the forward mapping from left to right followed by median filtering to obtain the HR depth map. Lee and Lee [17] found that the depth reconstruction and super resolution of LR stereo images are interrelated, so they proposed the problem of super resolving intensity and depth under a single framework and solved using first-order primal dual algorithm.…”
Section: Sr For Multiple Images and Single Imagementioning
confidence: 99%
“…Low-resolution (LR) input images also often affect stereo matching accuracy [5,15], because low-quality cameras are frequently used considering the limitations in cost or space for some applications. However, even in a highresolution (HR) image, the actual scene resolution is spatially uneven and dependent on depth because of the perspective projection.…”
Section: Introductionmentioning
confidence: 99%